2019
DOI: 10.3389/fsufs.2019.00056
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Farmers Spend Credit Primarily on Food: Gender Differences and Food Security Implications in a Changing Climate

Abstract: In many low-income nations agriculture is used as the primary source of income, which in the face of a changing climate, is known to be at considerable risk for the smallholder farmers that rely on it. Financial resources may enable smallholder farmers to implement adaptation practices and diversify income and investments, which has the potential to affect household income and food security. Here we explore relationships between access to different types of financial resources among male and female-headed hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
(68 reference statements)
2
19
0
Order By: Relevance
“…Twenty‐two articles explored the risk factors to vulnerability in relation to women's health and climate change (Alhassan et al., 2019 ; Balehey et al., 2018 ; Beaumier & Ford, 2010 ; Bunce et al., 2016 ; Carranza & Niles, 2019 ; Denton, 2002 ; Khapung, 2016 ; Koehler, 2016 ; Larson et al., 2018 ; Leipert & Reutter, 2005 ; MacVicar et al., 2017 ; Marí‐Dell'Olmo et al., 2019 ; Mason & Agan, 2015 ; Masson et al., 2019 ; Mazorra et al., 2020 ; Ortega‐Egea et al., 2014 ; Poudel et al., 2020 ; Roy & Venema, 2002 ; Seidel & Bell 2014 ; Shanthi et al., 2017 ; Shodieva et al., 2014 ; Singh et al., 2018 ). Climate change exacerbated existing gender and social inequalities faced by women, especially in rural and remote communities (Alhassan et al., 2019 ; Balehey et al., 2018 ; Beaumier & Ford, 2010 ; Bunce et al., 2016 ; Khapung, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty‐two articles explored the risk factors to vulnerability in relation to women's health and climate change (Alhassan et al., 2019 ; Balehey et al., 2018 ; Beaumier & Ford, 2010 ; Bunce et al., 2016 ; Carranza & Niles, 2019 ; Denton, 2002 ; Khapung, 2016 ; Koehler, 2016 ; Larson et al., 2018 ; Leipert & Reutter, 2005 ; MacVicar et al., 2017 ; Marí‐Dell'Olmo et al., 2019 ; Mason & Agan, 2015 ; Masson et al., 2019 ; Mazorra et al., 2020 ; Ortega‐Egea et al., 2014 ; Poudel et al., 2020 ; Roy & Venema, 2002 ; Seidel & Bell 2014 ; Shanthi et al., 2017 ; Shodieva et al., 2014 ; Singh et al., 2018 ). Climate change exacerbated existing gender and social inequalities faced by women, especially in rural and remote communities (Alhassan et al., 2019 ; Balehey et al., 2018 ; Beaumier & Ford, 2010 ; Bunce et al., 2016 ; Khapung, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…They were identified as often being the last members to eat in the household, allowing the males in the family and the children to eat first (Bunce et al., 2016 ; Leipert & Reutter, 2005 ; Masson et al., 2019 ; Ortega‐Egea et al., 2014 ). The studies overall reported that women in general had very limited rights in owning land, wealth and were often excluded from inheritance (Balehey et al., 2018 ; Beaumier & Ford, 2010 ; Carranza & Niles, 2019 ; Denton, 2002 ; Koehler, 2016 ; Leipert & Reutter, 2005 ; MacVicar et al., 2017 ; Mason & Agan, 2015 ; Masson et al., 2019 ; Roy & Venema, 2002 ; Shanthi et al., 2017 ; Shodieva et al., 2014 ; Singh et al., 2018 ). Women's health and their role as caregivers are significantly affected by their lack of human rights, exclusion from decision making in society, and financial dependence on males who earn income in their households (Masson et al., 2019 ; Ortega‐Egea et al., 2014 ; Poudel et al., 2020 ; Roy & Venema, 2002 ; Singh et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, using HFCS may result in the highest food insecurity levels for household relying on farm-sourced food items. Although, in general, female-headed households are often behind male-headed households with regard to FS status [ 42 , 45 ], behavioral differences between women and men result in differences with respect to how financial resources are spent in male and female-headed households [ 46 ]. While female decision-makers may choose to invest their financial resources in food expenditures, male decision-makers may spend their financial resources on non-food items.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving sustainable agricultural growth remains to be a key driver of economic development and poverty reduction in many countries and contexts across the globe (Ogundeji et al , 2018). This is in view of the recognition that the sector serves as a primary source of household income (Carranza and Niles, 2019), food and raw materials for industries. Considering the rapidly increasing population and the demand for adequate and safe food to ensure food and nutrition security, the agricultural sector is expected to deliver a lot.…”
Section: Introductionmentioning
confidence: 99%